THE EFFECTIVENESS OF TEACHING ASSISTANCE IN IMPROVING STUDENTS’ PEDAGOGICAL COMPETENCE AT UIN DATOKARAMA PALU - Najla Abdul Ilah Badjeber; Arifuddin M. Arif; Naima; Darmawansyah; Jihan (Referensi Islamika: Jurnal Studi Islam, 2026)
This study explores how the Teaching Assistance Program at Educational Units (Asistensi Mengajar pada Satuan Pendidikan/AMSP) supports the development of pedagogical competence among Islamic Religious Education (PAI) students at the Faculty of Tarbiyah and Teacher Training, UIN Datokarama Palu. The study addresses the gap between campus-based pedagogical theory and students’ classroom practice, with attention to the integration of Islamic values in teaching. This research used a descriptive qualitative approach. Data were collected through semi-structured interviews with eight PAI students, two cooperating teachers, and one school principal, supported by document analysis of AMSP technical guidelines, lesson plans, logbooks, and program reports, as well as non-participant observation. Data were analyzed through reduction, display, and conclusion drawing, with credibility strengthened through source triangulation, technique triangulation, and member checking. The findings indicate that AMSP supported the development of students’ pedagogical competence in three main areas: lesson planning became more contextual and realistic; teaching implementation shifted toward more active and innovative learning; and learning assessment became more comprehensive by covering cognitive, affective, and psychomotor domains. The main constraints were limited formal coordination between university supervisors and cooperating teachers, early classroom management difficulties, administrative workload, and curriculum adjustment challenges. The findings are limited to PAI students, selected partner schools, and one academic period. Because the study used a qualitative design, the results should be understood as evidence of perceived and observed pedagogical development rather than a statistical measure of program contribution. This study contributes to the conceptual discussion of field experience, pedagogical competence, Islamic value integration, and pre-service PAI teacher formation within Islamic higher education.